The Relationship of Diet and Hygiene to the Incidence of Tonsillitis in Children: A Literature Review - Naila, Fakhirah; Warasanti, Endang Susanti (Journal of Diverse Medical Research: Medicosphere, 2025)
Background: Everyone has tonsils that can become problematic for some reason. Tonsillitis is an inflammation of the tonsils that occurs due to infection. Inflammation of the tonsils can cause discomfort and difficulty swallowing. These conditions cause disruption to daily activities. The incidence of tonsillitis in Indonesia is still quite high, especially in children aged 5-15 years. Tonsillitis itself is the second highest case in the ear nose and throat (ENT) field. Tonsillitis can occur due to several factors, one of which is closely related to diet and oral hygiene. This article is to determine the relationship between diet and oral hygiene on the incidence of tonsillitis in children. Methods: The method used was a literature review taken from several sources from 2019-2024. Database for this article such as PubMed, Google Scholar, and Science Direct. The search keywords we used were diet, hygiene, tonsillitis, and child. Discussion: The highest incidence of tonsillitis in children is due to the body's imperfect immune response. This is supported by children's low knowledge of unhealthy diets such as eating fast food and preservatives. In addition, oral hygiene also contributes to the risk of tonsillitis where children cannot maintain their own hygiene such as washing hands before eating and brushing teeth twice a day. Conclusion: There is an association between diet and oral hygiene to tonsillitis supported by the immune system that is still in the developmental stage in children.